Determination of Gender Differential Item Functioning in Tegal Students' Scientific Literacy Skills with Integrated Science (SLiSIS) Test Using Rasch Model - Susongko, P.; Arfiani, Y.; Kusuma, M. (Jurnal Pendidikan IPA Indonesia, 2021)
The emergence of Differential Item Functioning (DIF) indicates an external bias in an item. This study aims to identify items at scientific literacy skills with integrated science (SLiSIS) test that experience DIF based on gender. Moreover, it is analyzed the emergence of DIF, especially related to the test construct measured, and concluded on how far the validity of the SLiSIS test from the construct validity of consequential type. The study was conducted with a quantitative approach by using a survey or non-experimental methods. The samples of this study were the responses of the SLiSIS test taken from 310 eleventh-grade high school students in the science program from SMA 2 and SMA 3 Tegal. The DIF analysis technique used Wald Test with the Rasch model. From the findings, eight items contained DIF in a 95 % level of trust. In 99 % level of trust, three items contained DIF, items 1, 6, and 38 or 7%. The DIF is caused by differences in test-takers ability following the measured construct, so it is not a test bias. Thus, the emergence of DIF on SLiSIS test items does not threaten the construct validity of the consequential type.